Relationship between Aspalathus linearis (Burm. F.) R. Dahlgren (rooibos) growth and soil moisture in a glasshouse and in the DSSAT-CSM crop model - Adaramola, Rhoda Fiyinfoluwa (Department of Biological Sciences, 2021)
Climate change and drought pose a major threat to agriculture and water resources globally and for rooibos (Aspalathus linearis (Burm. F.) R. Dahlgren) production in the Western Cape province of South Africa. Rooibos is adapted to the coarse, nutrient poor, acidic, well-drained, deep sandy soil of the Fynbos biome. The region has a Mediterranean climate, which is characterised by wet cold winters, with an average annual rainfall of about 375 mm, and dry summers. The growth of rooibos peaks in the summer months, implying a reliance on soil moisture. The current study aims to investigate the relationship between rooibos growth and soil moisture. The objectives of the study were: 1) to determine the effect of soil moisture on growth and evapotranspiration in rooibos under glasshouse conditions, 2) to adapt the CROPGRO model in DSSAT to simulate the shoot biomass yield of rooibos, using the rooibos CROPGRO model, 3) to investigate the effect of rooibos growth on soil moisture, and 4) to determine the effect of different levels of mulching and irrigation on rooibos yield and soil moisture. Some of the results obtained in the glasshouse study in Objective 1 and observational field data from the literature were used in the adaptation of the CROPGRO model. The glasshouse study was carried out at the University of Cape Town, using soils from Clanwilliam and Citrusdal sites to grow rooibos seedling for 16 weeks in pots before exposing them to drought treatments. The pots were arranged on trays in the glasshouse using a completely randomized design. Two drought treatments were used: moderate drought stress (MDS), set at 20% FC, and severe drought stress (SDS), during which watering was completely withdrawn, were applied to 10 pots per treatment per site. Data on plant growth, root morphology, evapotranspiration, soil moisture, chlorophyll fluorescence and leaves to determine chlorophyll and carotenoid concentration were collected from the plants in the glasshouse after 10 days of these drought treatments. The SDS plants were re-watered for 8 weeks for recovery, and together with the MDS and control plants were transferred into a growth chamber for measurement of gas exchange parameters and biomass. The CROPGRO model in DSSAT was adapted for rooibos by changing some parameters in a pigeon pea (Cajanus cajan L. Millspaugh) CROPGRO model. The adapted rooibos model was used to set up an experiment that compared the cumulative evapotranspiration and soil moisture from the rooibos field and bare soil under rainfed conditions. Also, in a simulation experiments, the model was used to determine the effect of three levels of mulching by means of wheat residue at 8000 kg/ha, 4000 kg/ ha and 2000 kg/ha and drip irrigation at 25.4mm and at 12.5mm once a week from December to March, both separately and in combination, on rooibos shoot biomass and soil moisture. The results from the glasshouse study showed a 40% decrease in biomass under MDS conditions for 12 weeks, while SDS plants could not survive beyond 10 days in the glasshouse. Root morphological features changed under severe drought stress, resulting in longer and thinner roots relative to the control plants. The reduced biomass accumulation under drought conditions was followed by reduced photosynthesis, stomata conductance, transpiration, and concentration of chlorophyll and carotenoids. Changes in both maximum quantum efficiency of photosystem II (Fv/Fm) and fluorescence quantum yield (Fq'/Fm') were observed in the later stages of the SDS plants (days 9 and 10) compared to the control plants but were unaltered in the MDS plants. The soil moisture correlated negatively with evapotranspiration and stomata conductance in control plants, while these relationships were absent in MDS plants. Changes in temperature in the glasshouse correlated positively with stomata conductance and transpiration in the control plants, but these correlations were also absent in MDS plants. However, changes in temperature correlated negatively with soil moisture in both the control plants and the MDS treated plants. The CROPGRO model in DSSAT was successfully adapted to simulate shoot biomass in rooibos under field conditions and the rooibos model had an agreement of 94% with observational shoot biomass under field conditions. Furthermore, the model simulated cumulative evapotranspiration in rooibos plants in the field, with an agreement of 56%. The simulated experiments showed that cumulative evapotranspiration from the rooibos field was 33% higher than that of bare soil, and showed that rooibos plants extract moisture from deep soil layers to a depth of about 2 m. Furthermore, rooibos growth in deep soil, and in mulched or irrigated treatments, produced higher shoot biomass than control plants. In deep soil, the simulated irrigated rooibos plants, which received 25.4 mm water weekly from December to March, produced a higher biomass yield than only rainfed or mulched plants. However, the combined treatments of mulching at 8000 or 4000 kg/ha and irrigation at 12.5 mm was similar to irrigation at 25.4mm. The average extractable soil moisture was greater in deep soil for all the treatments and control plants compared to shallow soil. Overall, the rooibos crop model shows that an increased supply of soil moisture enhances the production of biomass yield in rooibos in the field. Also, rooibos extracts moisture from a deeper soil layer, which enables it to hydrate its leaves and to transpire during the summer period for better growth and biomass production. Water loss through evapotranspiration was high in rooibos fields, and thus mulching of the plants would be beneficial for increased biomass production. However, even better rooibos yields were obtained when mulching was combined with irrigation. The glasshouse experiments showed a yield decrease of rooibos biomass by about 40% when the moisture supply was reduced by about 50% of the adequate conditions. The thinner and longer roots of rooibos, among other drought tolerance traits, most likely enable it to cope with low rainfall and drought conditions, which are prevalent in the Cederberg region of the Western Cape. The production of rooibos in the farms is prone to water loss through evapotranspiration, and thus soil moisture conservation technologies such as mulching would greatly enhance its biomass yield.